Uma nova abordagem termoeconômica para o tratamento de equipamentos dissipativos - Lourenço, Atilio Barbosa (2012)
The goal of this work is to present an alternative thermoeconomic approach whose application to refrigeration cycles should isolate dissipative components, as condensers and valves, in the productive structure so the yielded results are consistent. The approach, called UFS Model, is based on the concept of physical exergy splitting into three components, namely, internal energy term, flow work term and entropic term and is applied to five refrigeration cycles, namely, Carnot s reverse cycle, vapor-compression simple cycle, vaporcompression cascade cycle, vapor-compression cycle with intercooling and simple-effect absorption cycle. The cost balances are assessed at the components level and the exergetic unit costs of both internal flows and plant product are obtained. Also, the exergy analysis is done and compared with the difference of fuel (or resource) and product of each physical unit, besides the assessment of the product-resource ratios. The results show that the exergetic unit costs are never less than one and the product-resource ratios are never greater than 100%. Besides, the exergy analysis yields same irreversibility values of the difference of resource and product. Finally, some remarks are done as well as suggestions for future Works